Peningkatan Kualitas Pembelajaran melalui Optimalisasi Sumberdaya Manusia dalam Implementasi Kurikulum Merdeka - Kasmawati, Kasmawati; Nasir, Nasir; Bagea, Ishak; Fatmawati, Titi (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This research focuses on the challenges in implementing the Independent Curriculum at SD Negeri 5 Konda as well as efforts to optimize educational human resources (HR) to improve the quality of learning. The research method used is a descriptive qualitative approach with data collection through structured interviews, participant observation and document analysis. This research involved teachers and school principals as research subjects. The research results show that the main challenges in implementing the Merdeka Curriculum include teachers' limited time to participate in training, skills gaps in using technology, and high administrative burdens. Another challenge is limited infrastructure, especially in rural schools, which affects the effectiveness of the use of technology in learning. The proposed optimization strategies include practice-based training, digitalization of administrative tasks, and increased inter-teacher collaboration. The role of the principal is also very important in supporting and providing resources for teachers. The implication of this research is that by optimizing human resources through a planned strategy, the implementation of the Independent Curriculum can run more effectively, which will ultimately improve the quality of learning in elementary schools.